EFEKTIVITAS PENDEKATAN SAVI PADA MATERI LINGKARAN KELAS VIII SMP NEGERI 01 PONTIANAK - Agnes Ervinda Noventika; Bistari Bistari; Hamdan Hamdan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) approach on mathematics learning especially the material of bowstring length and area of circle in class VIII-A of SMP Negeri 01 Pontianak. Type of this research is one shot case study experiment. The research subjects in this study were students of class VIII-A SMP Negeri 01 Pontianak that selected by simple random sampling technique. Data collection was carried out using observation methods both teacher and students during the learning process, test, questionnaire, and documentation methods. The result of the research carried out obtained the result of calculations for organizing learning by 3.38 on scale of 1-4, which means that the teacher is classified as good in organizing learning. The activities of student during the learning process with the SAVI approach amounted to 72.98% with student’s responses to the learning process is 77.95%, which mean that students are active and respond to learning well. For this reason, the learning outcomes obtained are also classified as good with a percentage of 82%. So, the conclusion that the SAVI approach is effectively used in the learning process for circle subject matter of class VIII-A SMP Negeri 01 Pontianak. Keywords: Effectiveness of Learning, SAVI (Somatic, Auditory, Visual, Intelectual) Approach, Organizing Learning, Students Activities, Learning Outcomes